A chief HR officer's perspective on talent management. Issue 4 (7th November 2017) - Alziari, Lucien
Abstract : Purpose: The HR function has been through a palette of names and identities, with talent management or human capital management being one more. There is a lack of consistency in the way that HR practitioners think about talent management and this is often the cause of credibility issues with business colleagues. The purpose of this paper is to identify core beliefs that underpin the practice of talent management if the function is to build credibility. Design/methodology/approach: The paper identifies five core beliefs that should structure a discussion around, and underpin, the practice of talent management: notions of human capital management; questions about whether talent is generic or not; distinctions between talent management and HRM; decisions about who makes decisions about talent management; and moments of truth. It uses the case setting of Maersk to illustrate these beliefs and position the preferred conduct of talent management against them. Findings: Organizations make distinctions between where good (not average) is "good enough" and where they need world-class talent to drive true competitive advantage. This capability perspective results in three different clusters of effort in terms of talent management. They manage investments so that they do not over-invest in less critical capabilities but can marshal scarce resources in areas where they need to be world class. Practical implications: What is defined as talent in one setting might not be so in others. Strategies define capabilities and capabilities define talent. Attention must be given to all the other processes that support the deployment of talent to build specific organizational capabilities. As talent decisions are made by business leaders there needs to be a common mindset and decision-making logic for them to use. The 9 Box model is one such logic. Adopting any decision logic does not denote the outcome, rather it is how companies use the tool that determines the output. Originality/value: The paper positions talent management within the strategic management discipline of business models and analysis of how organizations need to compete. It uses an industrial setting and professional experience base to link talent management to the wider management of organizational capabilities.